Perceptions of Yoga Therapy Embedded in Two Inpatient Rehabilitation Hospitals: Agency Perspectives - Marieke Van Puymbroeck (Evidence-Based Complementary and Alternative Medicine, 2015)
Inpatient medical rehabilitation has maintained a typical medical-model focus and structure for many years. However, as integrative therapies, such as yoga therapy, emerge as treatments which can enhance the physical and mental health of its participants, it is important to determine if they can be easily implemented into the traditional rehabilitation structure and milieu. Therefore, the purpose of this study was to examine the perceptions of key agency personnel on the feasibility and utility of yoga therapy implemented in inpatient rehabilitation. This study reports the results of focus groups and an individual interview with key stakeholders (administrators and rehabilitation therapists) from two rehabilitation hospitals following the implementation of yoga therapy. Results focused on several key themes: feasibility from the therapist and administrator perspectives, challenges to implementation, and utility and benefit. Overall, the implementation and integration of yoga therapy were positive; however, some programmatic and policy and organizational considerations remain. Implications for practice and future research are provided.